Immobilization Screening and Characterization of an Alcohol Dehydrogenase and its Application to the Multi-Enzymatic Selective Oxidation of 1,-Omega-Diols - Santiago-Arcos, Javier; Velasco-Lozano, Susana; Diamanti, Eleftheria; Cortajarena, Aitziber L.; López-Gallego, Fernando (Frontiers in Catalysis, 2021)
Alcohol dehydrogenase from Bacillus (Geobacillus) stearothermophilus (BsADH) is a NADH-dependent enzyme catalyzing the oxidation of alcohols, however its thermal and operational stabilities are too low for its long-term use under non-physiological conditions. Enzyme immobilizations emerges as an attractive tool to enhance the stability of this enzyme. In this work, we have screened a battery of porous carriers and immobilization chemistries to enhance the robustness of a His-tagged variant of BsADH. The selected carriers recovered close to 50% of the immobilized activity and increased enzyme stability from 3 to 9 times compared to the free enzyme. We found a trade-off between the half-life time and the specific activity as a function of the relative anisotropy values of the immobilized enzymes, suggesting that both properties are oppositely related to the enzyme mobility (rotational tumbling). The most thermally stable heterogeneous biocatalysts were coupled with a NADH oxidase/catalase pair co-immobilized on porous agarose beads to perform the batch oxidation of several 1,-diols with in situ recycling of NAD+. Only when His-tagged BsADH was immobilized on porous glass functionalized with Fe3+, the heterogeneous biocatalysts oxidized 1,5-pentanediol with a conversion higher than 50% after 5 batch cycles. This immobilized multi-enzyme system presented promising enzymatic productivities towards the oxidation of several diols. Hence, this strategical study accompanied by a functional and structural characterization of the resulting immobilized enzymes, allowed us selecting an optimal heterogeneous biocatalyst and their integration into a fully heterogeneous multi-enzyme system